A Tandem Conjugate Addition–Intramolecular Horner–Wadsworth–Emmons Olefination Approach to the Synthesis of Cyclopentene[c]chroman-2-ones and Cyclopent-1-enecarboxylates - Deredas, Dariusz; Huben, Krzysztof; Maniukiewicz, Waldemar; Krawczyk, Henryk (Synlett, 2014)
A strategically new approach to cyclopentene[c]chroman-2-ones and cyclopent-1-enecarboxylates by tandem Michael–Horner–Wadsworth–Emmons reaction of 2,5-hexanedione with 3-(diethoxyphosphoryl)coumarins is described. The products were obtained as single diastereoisomers in high yields.
Keywords: Michael addition; Horner–Wadsworth–Emmons olefination; tandem reaction; annulations; 1,5,7-triazabicyclo[4.4.0]dec-5-ene